Labour Markets, Institutions and Inequality Building Just Societies in the 21st Century - Berg, Janine (Edward Elgar Publishing, 2015)
Labour market institutions, including collective bargaining, the regulation of employment contracts and social protection policies, are instrumental for improving the well-being of workers, their families and society. In many countries, these institutions have been eroded, whilst in other countries they do not exist at all. Labour Markets, Institutions and Inequality includes empirical case studies, from both developed and developing countries, which examine the role of institutions in ensuring equitable income distribution. The volume discusses the effect of macroeconomic, labour and social policies on inequality, highlighting how specific groups such as women, migrants and younger workers are affected by labour market institutions. Expert contributions demonstrate that in order to reduce inequality, countries must strengthen their labour market institutions through comprehensive policy formulation.